Political Communication Research: An Overview of the Past and the Present - Abdul Muneer V (COMMUNICATION & JOURNALISM RESEARCH, 2012)
The past and the current states of nature of political communi- cation research and its possible future directions have already been well documented by scholars like Anne Johnston (1990), Lynda Lee Kaid (2004), and Doris A Graber (2005). Based on their works, this article presents a panoramic view of the field of political communication research highlighting its scope, significance, theoretical and methodological developments, and major findings. Only major sub-fields such as Election Communication, Agenda setting, Political Learning, Priming and Framing, Political Rhetoric, Political Advertising, Political Campaign Debates etc. are covered in this review. The bibliography of this review may benefit the new entrants to the field.